2011
DOI: 10.1161/atvbaha.111.225573
|View full text |Cite
|
Sign up to set email alerts
|

Neointima Formed by Arterial Smooth Muscle Cells Expressing Versican Variant V3 Is Resistant to Lipid and Macrophage Accumulation

Abstract: Objective Extracellular matrix (ECM) of neointima formed following angioplasty contains elevated levels of versican, loosely arranged collagen, and fragmented deposits of elastin, features associated with lipid and macrophage accumulation. ECM with a low versican content, compact structure and increased elastic fiber content can be achieved by expression of versican variant V3, which lacks chondroitin sufate (CS) glycosaminoglycans (GAG). We hypothesized that V3-expressing arterial smooth muscle cells (ASMC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 50 publications
(57 reference statements)
0
57
0
Order By: Relevance
“…We also reported that this phenomenon contributes to the development of arterial stenoses in patients with Williams-Beuren syndrome and supravalvular aortic stenosis (17) as well as in patients with CS that develop severe hypertrophic cardiomyopathy (19). On the other hand, experimental induction of elastic fiber deposition in balloon-injured rabbit femoral arteries prevented formation of hyper-proliferative plaques (63). Also, we have established that the experimental induction of elastogenesis in astrocytoma cells cultures leads to decreased proliferation rate (64,65).…”
Section: Discussionmentioning
confidence: 92%
“…We also reported that this phenomenon contributes to the development of arterial stenoses in patients with Williams-Beuren syndrome and supravalvular aortic stenosis (17) as well as in patients with CS that develop severe hypertrophic cardiomyopathy (19). On the other hand, experimental induction of elastic fiber deposition in balloon-injured rabbit femoral arteries prevented formation of hyper-proliferative plaques (63). Also, we have established that the experimental induction of elastogenesis in astrocytoma cells cultures leads to decreased proliferation rate (64,65).…”
Section: Discussionmentioning
confidence: 92%
“…Deficiency in fibulin 2 and fibulin 5 in animals results in disrupted elastic laminae accompanied by an increase in vascular adhesion molecules and tissue factor expression as well as thrombus formation after carotid artery ligation injury (23), suggesting that the elastin-enriched ECM present in healthy aortas protects against vascular injury. Previously, we have demonstrated that expression of the V3 isoform of versican in ASMCs generates an ECM enriched in elastic fibers and that this ECM had reduced capacity to bind monocytes (4,18,19,28). We now show a causal relationship between changes in elastin accumulation and monocyte adhesion such that knocking down tropoelastin or fibulin 5, a component of microfibrils critical for elastic fiber formation (22)(23)(24), partially reverses the inhibition of monocyte adhesion caused by V3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we demonstrated that controlled expression of the V3 isoform of versican (V3) 2 by arterial smooth muscle cells (ASMCs), which lack glycosaminoglycan binding domains, reduced monocyte adhesion in vitro and monocyte/macrophage accumulation in vivo (4). However, the mechanism by which V3 expression reduces monocyte adhesion was not known.…”
Section: Monocyte/macrophage Accumulation Plays a Critical Role Durinmentioning
confidence: 99%
“…Moreover, oxLDL promote in AoSMC an ECM enriched in versican and most likely HA (which can account for increased monocyte binding in vitro (12)). Nevertheless, the existence of clear evidence that links oxLDL effects on ER stress and on ECM modification is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Merrilees et al (12) demonstrated in an in vivo model that monocytes localize in the atherosclerotic plaque in an HA-dependent manner and that the HA-rich ECM is promoted by the presence of oxidized LDL (oxLDL). Given the numerous oxidative events associated with the development of an inflammatory atherosclerotic plaque (13), LDL, which accumulate early in the intima primarily from enhanced retention by the glycosaminoglycans (1,12,14), are converted into aggregated LDL (aggLDL) (15) and/or oxLDL (16). OxLDL, in addition to the proper oxidized lipid products, also contains lysophospholipids, hydrolytic derivatives of oxidized phospholipids, prostanoids, isoprostanoids, leukotrienes, which are derived from the oxidation of arachidonic acid (17), and oxysterols (18), which contribute to reactive oxygen species generation and amplification of the steps described thus far (19).…”
mentioning
confidence: 99%